Pengaruh Penggunaan Jurnal Belajar Terhadap Hasil Belajar Mahasiswa Pendidikan Biologi STKIP-PI Makassar pada Mata Kuliah Perencanaan Pembelajaran - St Humaerah Syarif; Haris Munandar (Biota, 2018)
This research was quasi experimental with the purpose to determine the influence of using study journal toward study outcome of biology education students of STKIP-PI Makassar in lesson plan course. The research design is prestest-posttest control group design. The populations were students of Biology Education Program who conducting lesson plan of biologi subject in even semester (VI) of academic year 2017/2018. This research used random sampling technique to chose a control and an experimental class. The data collected by pretest and posttest. The data was collected analyzed by using descriptive and inferential statistic. The result showed that the average score of experimental class is 80,42 and control class is 75,33, standard deviation are 8,03 and 9,67. The result of hypotheses testing use Independent Samples T-test with SPSS for windows 20 program to get significance value is 0,03. The significance value 0,003 < α= 0,05, so H0 was rejected and H1 was accepted. It is showed that using study journal give positive influence to study outcome of biology education students of STKIP-PI Makassar in lesson plan course.